Secreted Glycoside Hydrolase Proteins as Effectors and Invasion Patterns of Plant-Associated Fungi and Oomycetes - Bradley, Ellie L.; Ökmen, Bilal; Doehlemann, Gunther; Henrissat, Bernard; Bradshaw, Rosie E.; Mesarich, Carl H. (Frontiers in Plant Science, 2022)
During host colonization, plant-associated microbes, including fungi and oomycetes, deliver a collection of glycoside hydrolases (GHs) to their cell surfaces and surrounding extracellular environments. The number and type of GHs secreted by each organism is typically associated with their lifestyle or mode of nutrient acquisition. Secreted GHs of plant-associated fungi and oomycetes serve a number of different functions, with many of them acting as virulence factors (effectors) to promote microbial host colonization. Specific functions involve, for example, nutrient acquisition, the detoxification of antimicrobial compounds, the manipulation of plant microbiota, and the suppression or prevention of plant immune responses. In contrast, secreted GHs of plant-associated fungi and oomycetes can also activate the plant immune system, either by acting as microbe-associated molecular patterns (MAMPs), or through the release of damage-associated molecular patterns (DAMPs) as a consequence of their enzymatic activity. In this review, we highlight the critical roles that secreted GHs from plant-associated fungi and oomycetes play in plant‒microbe interactions, provide an overview of existing knowledge gaps and summarise future directions.